2020
DOI: 10.2147/ijn.s252515
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Immunoenhancement Effects of Polyethylenimine-Modified Chinese Yam Polysaccharide-Encapsulated PLGA Nanoparticles as an Adjuvant</p>

Abstract: Background: Poly(lactic-co-glycolic acid) (PLGA) has been extensively applied for sustained drug delivery and vaccine delivery system. However, vaccines delivered by PLGA nanoparticles alone could not effectively activate antigen-presenting cells (APCs) to induce strong immune responses. Purpose: The aim of the present study was to design polyethylenimine (PEI)-modified Chinese yam polysaccharide (CYP)-encapsulated PLGA nanoparticles (CYPP-PEI) as a vaccine delivery system and evaluate the adjuvant activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Recently, natural polysaccharides have attracted a great deal of attention due to their advantages in synergistic and detoxifying effects. In addition, their potential biological activities, such as, immunomodulatory, antioxidant, antitumor, anti-inflammatory, antidiabetic, and antiviral activities, are being realized [ 52 , 53 ]. However, extraction methods affect not only yield but also the bioactivity of polysaccharides [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, natural polysaccharides have attracted a great deal of attention due to their advantages in synergistic and detoxifying effects. In addition, their potential biological activities, such as, immunomodulatory, antioxidant, antitumor, anti-inflammatory, antidiabetic, and antiviral activities, are being realized [ 52 , 53 ]. However, extraction methods affect not only yield but also the bioactivity of polysaccharides [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese yam polysaccharide PLGA nanoparticles (CYPPs) were prepared by a similar procedure without PEI. Our previous study reported the particle size and ζ potential of PEI-CYPP to be 236.6 nm and +41.5 mV, while the CYPP had a particle size of 225.0 nm and a ζ potential of −20.7 mV …”
Section: Methodsmentioning
confidence: 97%
“…Reproduced with permission. [ 60 ] Copyright 2021, Dove Medical Press Ltd. b) The structural assembly diagram of transient thermal response block copolymer nanoparticles encapsulated amphotericin B (AmpB). Reproduced with permission.…”
Section: The Types Of Adjuvantsmentioning
confidence: 99%
“…[59] Zhang et al designed polyethyleneimine (PEI) modified yam polysaccharide (CYP)-coated PLGA nanoparticles (CYPP-PEI) as a vaccine delivery system (Figure 3a). [60] And the results showed that it improved the efficiency of antigen absorption, promoting the uptake of antigen by macrophages and enhancing the activation of macrophages. It is beneficial to deliver antigen and CYP immunomodulators to lymph nodes and activate DCs, further enhancing Th1/Th2 mixed but Th1 biased immune responses in vivo.…”
Section: Polymer Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation